Supracondylar nailing for difficult distal femur fractures. - Saw, A.; Lau, C.P. (2003)
Supracondylar nailing for fixation of supracondylar (Arbeitsgemeinschaft für Osteosynthesefragen [AO] type A) and less comminuted intercondylar (AO type C1 and C2) fractures is recommended by the authors.